2018
DOI: 10.1007/s40258-018-0447-x
|View full text |Cite
|
Sign up to set email alerts
|

Peristeen Transanal Irrigation System to Manage Bowel Dysfunction: A NICE Medical Technology Guidance

Abstract: The Peristeen transanal irrigation system is intended to allow people with bowel dysfunction to flush out the lower part of the bowel as part of their bowel management strategy. Peristeen was the subject of an evaluation by the National Institute for Health and Care Excellence, through its Medical Technologies Evaluation Programme, for the management of bowel dysfunction. The company, Coloplast, submitted a case for adoption of the technology, claiming that the technology improves the severity of chronic const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 30 publications
(19 reference statements)
2
11
0
2
Order By: Relevance
“…Transanal irrigation (TAI) has received increasing attention as a treatment option in patients with bowel dysfunction as it has shown to improve faecal incontinence (FI) and chronic constipation (CC) [ 1 , 2 ]. With TAI, water is introduced into the bowel through the anus, facilitating emptying of the rectosigmoid and the left colon [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transanal irrigation (TAI) has received increasing attention as a treatment option in patients with bowel dysfunction as it has shown to improve faecal incontinence (FI) and chronic constipation (CC) [ 1 , 2 ]. With TAI, water is introduced into the bowel through the anus, facilitating emptying of the rectosigmoid and the left colon [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perspectives for further research include confirmation of these results in a larger population, such as a European-wide study of efficacy and safety in different healthcare systems. Furthermore, the device's cost-effectiveness remains to be assessed, although this is also the case for established devices such as the Peristeen® [8].…”
Section: Study Limitations and Strengthsmentioning
confidence: 99%
“…However, the rectum and distal portion of the sigmoid colon can be emptied by introducing water into the anus (typically through a balloon catheter or a cone catheter). This transanal irrigation (TAI) procedure can enable a patient to schedule the regular evacuation of stools, and thus enhance his/her activities of daily living [5][6][7][8]. For example, it has been reported that TAI over a 6-month period led to a significant improvement in quality of life for patients with low anterior resection syndrome [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, transanal irrigation (TAI) can be proposed as a different conservative treatment also in children with bowel dysfunction unresponsive to more conventional therapies such as enema or laxatives. TAI involves a large volume water irrigation of the rectum and the left colon, passing a catheter with a balloon as an anchor through the anus [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%